2008
DOI: 10.1097/mph.0b013e318158343b
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine-induced Peripheral Neuropathy and Urinary Bladder Paralysis in a Child With Rhabdomyosarcoma

Abstract: Vincristine commonly induces peripheral neuropathy but rarely causes voiding dysfunction. In this report, we describe a case of neurogenic bladder and peripheral neuropathy caused by the neurotoxic effect of vincristine and documented by urodynamic testing and electromyography. Neurologic evaluation aided in monitoring and understanding this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…7 The literature supporting VCR-induced bladder neuropathy is less robust; however, reports of suspected cases are published. 8,9 The clinical relevance of postchemotherapy LUTD manifests in the care of the pediatric cancer survivor. Recent decades have seen dramatic improvements in the 5-year survival rates of the most prevalent childhood cancers.…”
Section: Discussionmentioning
confidence: 99%
“…7 The literature supporting VCR-induced bladder neuropathy is less robust; however, reports of suspected cases are published. 8,9 The clinical relevance of postchemotherapy LUTD manifests in the care of the pediatric cancer survivor. Recent decades have seen dramatic improvements in the 5-year survival rates of the most prevalent childhood cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The novelty and significance of this study lie in the comprehensive description of all facets of vincristine-related NP: incidence, severity, and treatment; and in the exhaustive investigation of the associated risk factors, in the largest study to date in children treated for ALL. Previous studies of vincristine-induced neurotoxicity in children have been mainly case reports [10][11][12][13] and small series [14,15], and only race [16] and BMI [14] have been investigated as risk factors. We found that white non-Hispanic race is significantly predictive of vincristine-related NP, consistent with a previous study showing less neurotoxicity (4.8% versus 34.8%) and fewer reduced or missed vincristine doses in 21 black children than in 92 white non-Hispanic children with ALL [16].…”
Section: Discussionmentioning
confidence: 99%
“…VCR is an important part of many pediatric oncology treatment regimens; however, it is known to cause impairment of axonal transport, distal axonopathy and neuroinflammation, leading to VIPN 1 . Previously two clinical cases of the neurotoxic effects of VCR on LUT function; urinary bladder paralysis and detrusor areflexia, were reported 13 , 14 . In this study, the mice who received VCR demonstrated a decrease in micturition frequency and increased NVCs.…”
Section: Discussionmentioning
confidence: 99%